Harnessing Geographic Information Science for Global Health Security and Pandemic Preparedness - Jumoke I. Ogunremi; Nelson N. Igwilo; Oladayo O. Babalola (International Journal of Scientific Research in Science and Technology, 2024)
The growing frequency of infectious disease outbreaks highlights the urgent need for stronger global health security systems. Geographic Information Science (GIScience) offers powerful spatial tools to support pandemic preparedness by integrating data on disease dynamics, population vulnerabilities, and health system resources. This review examines the foundations and applications of GIScience in global health, focusing on its role in surveillance, outbreak mapping, transmission modeling, and resource allocation. It further explores the integration of GIScience with artificial intelligence, big data, and predictive analytics to enhance real-time decision-making during health emergencies. While these technologies offer substantial benefits, challenges remain in data quality, interoperability, privacy, and equitable access, particularly in low- and middle-income settings. The review also identifies gaps in policy and governance frameworks that hinder effective use of geospatial tools in international health strategies. Looking forward, emerging innovations such as geospatial artificial intelligence, digital twins, and global data-sharing networks demonstrate the transformative potential of GIScience for building resilient health systems. By synthesizing existing knowledge and outlining future research needs, this review emphasizes the critical role of GIScience as a cornerstone of pandemic preparedness and global health resilience.
Keywords: Geographic Information Science; Global Health; Security; Pandemic; Preparedness